Level of understanding on the concept of vaccination and practices among bentong residents / Maryam Hanisah Abdul Jalil - Abdul Jalil, Maryam Hanisah (2019)
Nowadays, vaccination has become a necessary part of public health and disease prevention, but it remains a contentious issue in today's culture. Diseases which were once responsible for significant morbidity and mortality have now become all but eradicated, thanks to the introduction of vaccines. In Malaysia, the smallpox vaccine was the first vaccine to be introduced in the early 1950s. It was accompanied by the triple antigen that continues today. Tetanus toxoid vaccination for pregnant women began in 1947, BCG was introduced in 1961, and polio vaccination was introduced in 1972 regarding a polio epidemic. Measles were introduced in 1982 and rubella vaccination for girls was introduced in 1985 while hepatitis B was introduced in 1989 for newborns. In this study, researcher aims to discussing the concept of vaccination and explain the practices of vaccination among Bentong residents. This study found that majority of people understands the concept of vaccination from the view towards the use of vaccines, ingredients of vaccines and the effect of vaccination and showed that majority of people have practiced vaccination and taken cognizance of the issues related to vaccination such as substance that are used and the effect of the vaccine. Majority of contemporary fuqaha permit the practices of vaccination based on their ijtihad to provide maslahah among the society. Vaccination policies can be strengthening by government through enforcement of vaccination to increase herd immunity and provide protection from infectious diseases. Therefore, this research was conducted by interviewed with informants from Bentong residents and document research.